Concrete containers in radioactive waste management: a review - Barbara Lacerda Tavares; Clédola Cássia Oliveira de Tello (Brazilian Journal of Radiation Sciences, 2019)
Nuclear power is considered a clean energy because it does not produce the gases responsible for greenhouse effect. However, like all human activities, it is susceptible to the generation of waste. With the increasing demand for energy in Brazil, the use of nuclear power is being expanded. With this, the implementation of proper treatment and disposal have become a necessity in order to ensure the non-contamination of the public or environment and that the exposure doses are lower than the limits determined by legislation. Most of the waste produced in Brazil is classified with low and intermediate radiation levels; consequently, the national repository will be near surface, in accordance with the legislation. Considering the multi-barrier concept for the repository, the radioactive waste product is the first barrier. To have a qualified radioactive waste product, it should be solid or solidified using an inert material. With the intention to standardize the disposal process, all radioactive waste products will be placed in concrete containers. These containers will be settled in a concrete cell, which is the final engineered barrier of the repository. The state of the art is the first part of the study of the concrete containers and its specific criteria acceptation. Tests still need to be performed in order to ensure the stability and resistance of the material, since the repository’s operational and surveillance period is 60 and 300 years respectively.